THE STUDY OF MALANG THEMATIC KAMPONG AS A POTENTIAL INTERNATIONAL TOURISM DESTINATION WITH THE GENIUS LOCI CONCEPT - Debri Haryndia Putri; Titi Ayu Pawestri (ARSITEKTURA, 2019)
Thematic Kampong is one of the government's efforts to overcome settlements problem aimed to improve the quality of the environment through the area arrangement and development based on the dynamic of local uniqueness and potency. Currently, Malang has about 78 Thematic Kampongs. So, the purpose of this research is to analyze the implementation of Genius Loci concept on the Malang Thematic Kampongs. The result of this analysis could be a guideline design to develop the Thematic Kampong into international tourism destinations in Malang. Therefore, this research is using qualitative descriptive method with phenomenology approached. To analyze the readiness of potential international tourism destination on all Thematic Kampongs, this research is using quantitative methods with questionnaire technique. The result shows that the 3G Kampong has succeeded in applying the concept of Genius Loci in its development and very potential to become an international tourist village.